Pengembangan Infrastruktur WisataBerbasis Komunitas dalam Mendukung EkowisataPantai Kaluku di Desa Limboro, Kabupaten Donggala - Wahyuningsih, Tri; Khairinrahmat; Muhammad Bakri; Adam, Andi Arham; Rahman, Yuli Asmi; Bakri; Maadji, Rizaldi; AR. Lamasitudju, Chairunnisa (Panrita Abdi - Jurnal Pengabdian pada Masyarakat, 2026)
The development of ecotourism requires adequate infrastructure and active community involvement. Kaluku Beach in Limboro Village, Donggala Regency, Central Sulawesi Province still faces limitations in terms of tourism infrastructure. This community service activity aims to develop community-based tourism infrastructure to support sustainable management of Kaluku Beach ecotourism. The implementation method uses the Participatory Action Learning System (PALS) approach, which emphasizes community participation, action-based learning, and strengthening sustainable systems through the stages of preparation, implementation, monitoring, and evaluation. In terms of process, the activity demonstrates active community participation in planning, implementation, and evaluation. This community service activity received positive response from partners because it succeeded in realizing the development and provision of infrastructure, including: the construction of gate as tourism area identity; the installation of solar-powered lights; the provision of Starlink satellite devices; the socialization of tourism industry digitization with the full participation of 15 members of the tourism awareness group (pokdarwis) and 70% active involvement; installation of coastal environmental awareness signboards; and map of community-based tsunami hazard and evacuation routes. In terms of sustainability, the activity concluded with the signing of a partnership agreement between the Faculty of Engineering at Tadulako University and the Limboro Village Government. Overall, this community service activity not only focused on providing infrastructure, but also on improving institutional capacity, community awareness, and disaster preparedness so that Kaluku Beach ecotourism can be managed independently and sustainably. Keywords: Tourism infrastructure, community, ecotourism, Kaluku Beach Pengembangan ekowisata memerlukan dukungan infrastruktur yang memadai serta keterlibatan aktif masyarakat. Pantai Kaluku di Desa Limboro, Kabupaten Donggala, Provinsi Sulawesi Tengah masih menghadapi keterbatasan infrastruktur pendukung wisata. Kegiatan pengabdian ini bertujuan mengembangkan infrastruktur wisata berbasis komunitas dalam mendukung pengelolaan ekowisata Pantai Kaluku secara berkelanjutan. Metode pelaksanaan menggunakan pendekatan Participatory Action Learning System (PALS) yang menekankan partisipasi masyarakat, pembelajaran berbasis aksi, dan penguatan sistem berkelanjutan melalui tahapan persiapan, pelaksanaan, monitoring dan evaluasi. Pada aspek proses, kegiatan menunjukkan partisipasi aktif masyarakat dalam perencanaan, pelaksanaan, dan evaluasi program. Kegiatan pengabdian ini memperoleh respon positif dari mitra karena berhasil mewujudkan pembangunan dan penyediaan infrastruktur, meliputi: pembangunan gapura sebagai identitas kawasan wisata; pemasangan lampu tenaga surya; penyediaan perangkat satelit Starlink; sosialisasi digitalisasi industri pariwisata dengan partisipasi penuh dari 15 anggota pokdarwis dan keterlibatan aktif 70%; pemasangan papan informasi dan edukasi lingkungan pesisir; serta tersusunnya peta bahaya tsunami dan jalur evakuasi berbasis komunitas. Pada aspek keberlanjutan, kegiatan ditutup dengan penandatanganan perjanjian kerja sama desa binaan antara Fakultas Teknik Universitas Tadulako dan Pemerintah Desa Limboro. Secara keseluruhan, kegiatan pengabdian ini tidak hanya berfokus pada penyediaan infrastruktur, tetapi juga meningkatkan kapasitas kelembagaan, kesadaran masyarakat, dan kesiapsiagaan bencana sehingga ekowisata Pantai Kaluku dapat dikelola secara mandiri dan berkelanjutan. Kata Kunci: Infrastruktur wisata, komunitas, ekowisata, Pantai Kaluku